Prognostic Value of Left Ventricular Diastolic Dysfunction in Patients Undergoing Cardiac Catheterization for Coronary Artery Disease - Hidekatsu Fukuta; Nobuyuki Ohte; Kazuaki Wakami; Toshihiko Goto; Tomomitsu Tani; Genjiro Kimura (Cardiology Research and Practice)
We hypothesized that left ventricular (LV) diastolic dysfunction assessed by cardiac catheterization may be associated with increased risk for cardiovascular events. To test the hypothesis, we assessed diastolic function by cardiac catheterization (relaxation time constant (Tau) and end-diastolic pressure (EDP)) as well as Doppler echocardiography (early diastolic mitral annular velocity (𝑒) and a ratio of early diastolic mitral inflow to annular velocities (𝐸/𝑒)) in 222 consecutive patients undergoing cardiac catheterization for coronary artery disease (CAD). During a followup of 1364 ± 628 days, 5 cardiac deaths and 20 unscheduled cardiovascular hospitalizations were observed. Among LV diastolic function indices, Tau > 48 ms and 𝑒<5.8 cm/s were each significantly associated with lower rate of survival free of cardiovascular hospitalization. Even after adjustment for potential confounders (traditional cardiovascular risk factors, the severity of CAD, and cardiovascular medications), the predictive value of Tau > 48 ms and 𝑒<5.8 cm/s remained significant. No predictive value was observed in EDP, 𝐸/𝑒, or LV ejection fraction. In conclusion, LV diastolic dysfunction, particularly impaired LV relaxation assessed by both cardiac catheterization and Doppler echocardiography, is independently associated with increased risk for cardiac death or cardiovascular hospitalization in patients with known or suspected CAD.